Detection and Identification of Banana-associated Phytoplasma Using Nested-PCR Method - Saurma Mona Astrid Sibarani; Tri Joko; Siti Subandiyah (Jurnal Perlindungan Tanaman Indonesia, 2019)
Phytoplasma is known to be associated with plant diseases in about 300 plant species from various families. Information on the presence of phytoplasma in bananas as one of the pathogens that can cause disease in bananas in Indonesia has never been reported. This research was conducted with the aim to detect the presence of banana phytoplasma by the nested-PCR method and to identify phytoplasma obtained based on the sequence analysis of the 16S rRNA gene. Standard PCR was carried out using P1/P7 primary pairs, followed by nested-PCR using a pair of R16F2n/R16R2m23SR primers separately that could amplify the target 16S rRNA genes in a row at 1600 bp. BLAST analysis shows that the results of phylogenetic analysis of banana phytoplasmic nucleotide cv. manggala from Tasikmalaya and cv. Raja nangka from Banjar has a genetic relationship that is closer to lethal wilt oil palm Phytoplasma (Candidatus Phytoplasma asteris). This phytoplasma belongs to the 16SrI-B group (aster yellows).